The map of Huesca of 1891 in the context of local intrigues and shortage of municipal finance - Villanova, José Luis (Geographicalia, 2017)
This paper discusses the process to develop the map of Huesca of 1891; the last of the five maps of the capital city provinces that was surveyed by Dionisio Casañal, topographer, between 1879 and 1891. The study has been made using original and in part unpublished documents and newspapers of the time, as well as literature on the history of urban cartography, the political characteristics of the Spain of the Restoration and the economy of municipal finances in that period of time. In the research is confirmed the high technical quality of the map and its profitable use in urban planning and management. It has also shown that the contract of this work was linked to partisan politics and it supposed an unreasonable burden on the meager municipal budgets.